Síntese e caracterização de catalisadores à base de cobre (Cu) e cério (Ce) suportados em nanotubos de carbono para aplicação na reação CO-PROX - Pinzón, Dayana Lizeth Sánchez (2019)
H2-based technologies are an efficient alternative for producing sustainable energy. Fuel cells are electrochemical devices that work with pure H2. Industrially, reforming of fossil fuels is the most used technology for obtaining hydrogen, however, the synthesis gas derived has an inappropriate CO content. The CO-PROX reaction is used to treat these streams. Noble metals are used as catalyzed, however some transition metals are being employed due to their high potential. In this sense, CuO and CeO2 based metal catalysts supported on carbon nanotubes (NTCs) were synthesized by wet impregnation. The precursors (CuO and CeO2) were selectively deposited on the inner and/or outer surface of the NTCs. The physicochemical properties of the catalysts were evaluated by N2 Physisorption, TGA, XRD, RAMAN Spectroscopy, TPD-He, TPR-H2, TPSR, SEM, MET and XPS and were tested in the CO-PROX reaction. The results confirmed the deposition of the metal precursors. CeO2 and CuO phases were detected with interplanar distances of 0.32 and 0.27 nm, respectively, and mean particle sizes in the range 4.5 – 8.0 nm for CeO2 and CuO. On the surface of the catalysts the species Ce4+ , Ce3+, Cu2+ and Cu1+ were identified. The interaction between the metal oxides and the internal surface of the NTCs favored the catalytic activity. The catalysts showed good activity and catalytic stability. The synthesis methodology was efficient, being able to control the selective deposition (internal and/or external surface of the NTCs) of CeO2 and/or CuO precursors.